2019
DOI: 10.1155/2019/5490413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MRSA Transmission and Infection in a Neonatal Intensive Care Unit in China: A Bundle Intervention Study during 2014-2017

Abstract: Objective. To evaluate the efficacy of bundle intervention on healthcare-associated (HA) methicillin-resistant Staphylococcus Aureus (MRSA) infection in the neonatal intensive care unit (NICU). Methods. In this study, 11,277 infants having undergone treatment at the NICU in Xiamen, China, from January 2014 to February 2017 were recruited. We retrospectively reviewed patients’ demographic and clinical information. Patients from 2014 to 2015 were treated as the control group and those from 2016 to 2017 were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The most common terms used in the publications to name the care bundles were 'measures' (13, 30%), 24,26,31,40,43,49,50,53,55,[57][58][59]61 followed by 'bundles' (nine, 21%). 20,23,27,30,34,35,37,41,47 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common terms used in the publications to name the care bundles were 'measures' (13, 30%), 24,26,31,40,43,49,50,53,55,[57][58][59]61 followed by 'bundles' (nine, 21%). 20,23,27,30,34,35,37,41,47 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The studies reported data from 55 LMIC, with India and China being most commonly represented ( Table 1 ). [20] , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Regarding study design, 24 (55%) were uncontrolled before-after, 20 , 21 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 32 , [33] , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 36 , 43 , 44 , 45 , 46 and two (5%) were interrupted time series. 47 , 48 The rest were retrospective outbreak investigation studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All VRE cases were reported from hospital wards. The ability of MRSA and VRE to spread from hospital environment to the patients as well as from other infected or colonised patients/ health care workers (14,15), coupled with immature immunologic functions in neonates (15), explains the frequent outbreaks in neonatal wards. Crowded schools and universities might create an environment to facilitate the spread of MRSA (16).…”
Section: Discussionmentioning
confidence: 99%